Ecology of Ephemeroptera, Plecoptera and Trichoptera (Insecta) in Rivers of the Gunung Jerai Forest Reserve: Diversity and Distribution of Functional Feeding Groups - Suhaila Ab Hamid; Che Salmah Md Raw (Tropical Life Sciences Research, 2014)
A field study was performed to describe the functional feeding groups (FFGs) of Ephemeroptera, Plecoptera and Trichoptera (EPT) in the Tupah, Batu Hampar and Teroi Rivers in the Gunung Jerai Forest Reserve (GJFR), Kedah, Malaysia. Twenty-nine genera belonging to 19 families were identified. The EPTs were classified into five FFGs: collector-gatherers (CG), collector-filterers (CF), shredders (SH), scrapers (SC) and predators (P). In this study, CG and CF were the dominant groups inhabiting all three rivers. Ephemeroptera dominated these rivers due to their high abundance, and they were also the CG (90.6%). SC were the lowest in abundance among all groups. Based on the FFGs, the Teroi River was suitable for CG, whereas the Tupah and Batu Hampar Rivers were suitable for CG and CF. The distribution of FFGs differed among the rivers (CG, ?2 = 23.6, p = 0.00; SH, ?sup>2 = 10.02, p = 0.007; P, ?sup>2 = 25.54, p = 0.00; CF, ?sup>2 = 21.95, p = 0.00; SC, ?sup>2 = 9.31, p = 0.01). These findings indicated that the FFGs found in rivers of the GJFR represent high river quality. Satu kajian lapangan telah dijalankan ke atas kumpulan pemakanan (FFG) bagi order Ephemeroptera, Plecoptera dan Trichoptera (EPT) di Sungai Tupah, Sungai Batu Hampar dan Sungai Teroi, di Hutan Simpan Gunung Jerai (GJFR), Kedah, Malaysia. Dua puluh sembilan genera daripada 19 famili telah dikenal pasti. EPT telah diklasifikasikan kepada lima FFG; pemungut-kumpul (CG), pemungut-turas (CF), pengoyak (SH), penyagat (SC) dan pemangsa (P). Daripada kajian ini, CG dan CF merupakan kumpulan dominan yang dijumpai di kesemua sungai. Ephemeroptera mendominasi sungai-sungai kerana ia mencatatkan bilangan tertinggi dan merupakan CG (90.6%). SC mencatatkan bilangan terendah di kalangan semua kumpulan. Sungai Teroi sangat sesuai untuk CG sahaja manakala Sungai Tupah dan Sungai Batu Hampar sesuai untuk CG dan CF. Perkadaran FFG adalah berbeza antara sungai-sungai (CG, ?2 = 23.6, p = 0.00; SH, ?2 = 10.02, p = 0.007; P, ?2 = 25.54, p = 0.00; CF, ?2 = 21.95, p = 0.00; SC, ?2 = 9.31, p = 0.01). Penemuan ini menunjukkan FFG yang dijumpai di sungai-sungai daripada GJFR mewakili sungai kelas tinggi.